Challenges and solutions to implementing education for sustainable development in geography classes: an international comparison of geography teachers’ perceptions (Germany-NRW and Iran) - Khademi, Somaye; Budke, Alexandra (Frontiers in Education, 2026)
This study examines the challenges and solutions related to implementing Education for Sustainable Development (ESD) in geography classes in two countries with different political and educational systems: Germany (North Rhine-Westphalia) and Iran. The research focuses on how teachers in both contexts perceive the integration of ESD into their teaching. A qualitative approach was used to conduct interviews with open-ended questions with 30 geography teachers from both countries to assess their perceptions of ESD implementation. The study identifies key barriers to implementing ESD and teacher-proposed solutions in three main categories: teaching practice, schools and educational organizations, and political and social framework conditions. The findings show that German teachers emphasized challenges and solutions more closely related to lessons, classes, and schools, such as curriculum-related issues. In contrast, Iranian teachers focused on challenges and solutions linked to the broader education system and national context. They highlighted the centralized education system and political and religious barriers.These results suggest that although there are barriers to ESD in both settings, the level at which they occur differs. German teachers concentrate on classroom and school structures, while Iranian teachers stress systemic, political, and societal constraints.